PENGETAHUAN IBU HAMIL TENTANG ANEMIA PADA KEHAMILAN DI POLINDES TANAK AWU WILAYAH KERJA PUSKESMAS SENGKOL KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH - Nining Fatria ningsih; Siti Maryam; Mustika Ayu Lestari; Jusmala Sari (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Based on PWS-KIA Sengkol Community Health Center in 2022 there were 1,011 pregnant women and the number of anemic pregnant women was 145 (14.34 %). There were 25 (11.11%) anemic pregnant women in Sengkol village, 24 (10.91%) anemic pregnant women in Kawo, 22 (23.91%) anemic pregnant women in Ketara, 26 (13.00%) anemic pregnant women in Tanak Awu. %) anemic pregnant women, Pengburur 38 (18.72%) anemic pregnant women, All Anyar 10 (13.08%). To find out the description of pregnant women's knowledge about anemia at the Tanak Awu Polindes, Sengkol Health Center Working Area, Central Lombok Regency 2023. The research method used was a descriptive method with the number of respondents being 43. Knowledge of Pregnant Women About Anemia was 22 respondents (52%) had sufficient knowledge, 14 respondents (33%) had good knowledge, and 7 respondents (16%) had poor knowledge.